Potential Involvement of Type I Interferon Signaling in Immunotherapy in Seasonal Allergic Rhinitis - Lina Mattson; Antonio Lentini; Danuta R. Gawel; Tejaswi V. S. Badam; Mikael Benson; Torbjorn Ledin; Colm E. Nestor; Mika Gustafsson; Jordi Serra-Musach; Janne Bjorkander; Zou Xiang; Huan Zhang (Journal of Immunology Research)
Specific immunotherapy (SIT) reverses the symptoms of seasonal allergic rhinitis (SAR) in most patients. Recent studies report type I interferons shifting the balance between type I T helper cell (Th1) and type II T helper cells (Th2) towards Th2 dominance by inhibiting the differentiation of naive T cells into Th1 cells. As SIT is thought to cause a shift towards Th1 dominance, we hypothesized that SIT would alter interferon type I signaling. To test this, allergen and diluent challenged CD4+ T cells from healthy controls and patients from different time points were analyzed. The initial experiments focused on signature genes of the pathway and found complex changes following immunotherapy, which were consistent with our hypothesis. As interferon signaling involves multiple genes, expression profiling studies were performed, showing altered expression of the pathway. These findings require validation in a larger group of patients in further studies.